2020
DOI: 10.1002/star.201900281
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Starch Storage Condition on Glycemic Index and Resistant Starch of Cooked Potato (Solanum tuberosum) Tubers

Abstract: Potato is a modified stem, which is rich in starch. Very often, potato is categorized as a high glycemic index (GI) food. Consuming high GI foods should be done with moderation to prevent insulinemic spikes, which can be a preventive measure against diabetes and related disorders. A modified, inexpensive, and precise in vitro method is developed for estimation of GI in potato tubers. Among the six varieties, Kufri Chipsona‐3 exhibits the highest GI (83.08) whereas Kufri Jyoti has the lowest value (72.87); the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
(63 reference statements)
3
25
0
Order By: Relevance
“…Our results of RS range in Indian potato varieties are in accordance with Lal et al. [ 18 ] Raigond et al. [ 6 ] have also reported low RS content in boiled tubers compared to microwave cooked and pressure cooked tubers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results of RS range in Indian potato varieties are in accordance with Lal et al. [ 18 ] Raigond et al. [ 6 ] have also reported low RS content in boiled tubers compared to microwave cooked and pressure cooked tubers.…”
Section: Resultssupporting
confidence: 91%
“…During boiling, starch gelatinization leads to increased digestion and hence less formation of RS takes place. Our results of RS range in Indian potato varieties are in accordance with Lal et al [18] Raigond et al [6] have also reported low RS content in boiled tubers compared to microwave cooked and pressure cooked tubers. Higher RS content in microwave cooked tubers as compared to boiled tubers as well as cultivar differences in the RS content of potatoes have been reported by Mulinacci et al [19] The RS concentration is also affected by the amylose content, amylose: amylopectin ratio and temperature during cooking and storage.…”
Section: Changes Due To Cookingsupporting
confidence: 91%
“…The electrical conductivity of soil more than 1.95 dSm −1 resulted in the rotting of seed tubers, which failed to achieve full emergence under salt stress [43]. Potato processing reduces post-harvest losses and over-production glut, thereby increasing farm income and ensuring the nation's food and nutritional security [61]. It is a well-known fact that potato cultivars having more than 21-23% dry matter can only be employed in processing industries.…”
Section: Effects Of Salt Stress On Potato Growth and Developmentmentioning
confidence: 99%
“…Further, ACHO in potato also affect glycemic response and this is defined in terms of glycemic load; GL. [15,16] The GL basically represents the equivalent GI of 1 g of carbohydrate as compared to a reference food. [16] Resistant starch (RS) is the portion of the starch that is least digested or not digested at all by the small intestine before it enters into the large intestine.…”
Section: Introductionmentioning
confidence: 99%